Negotiating conflict in deeply divided societies: complex power-sharing institutions in South Asia and Eastern Europe - Carciumaru, Radu (2019)
The thesis seeks to explain how and why power-sharing arrangements come into being, succeed or fail their purpose by combining negotiation theory with consociational power-sharing theory. The thesis compares case studies from South Asia (Punjab, Mizoram, in India and Sri Lanka) and Eastern Europe (Bosnia and Herzegovina, Transnistria and Gagauzia, in Moldova), while building its own model of negotiating conflict in deeply divided societies. All selected case studies experienced different intensities of violent ethnical conflicts that were or still are managed by different patterns of power-sharing arrangements. In case of the Eastern European states, various degrees of involvement of international actors have taken place. I analyze the (re)action and support of domestic actors in terms of efficacy and legitimacy of and involvement with central state institutions, perceived as de facto or de jure protectorates of the external powers. Despite the growing number of cases in which ethnic conflicts are regulated by means of consociational power-sharing arrangements relatively little systematic comparative work has been undertaken. By means of mutually enriching and reciprocally completing syntheses of different approaches to power-sharing based on the selected case studies I intend to add to as well as extend the existing body of knowledge. After the introduction and critical review of the literature, the thesis analysis case studies from South Asia and Eastern Europe. The thesis combines power-sharing and negotiation theories into a comprehensive theory of ethnic conflict management in deeply divided societies and develops a new model for successful negotiations in such settings. The analysis of each case study follows the levels-of-analysis approach and analytic narrative methods.